Predicting methods for sulfur removal from model oils using COSMO-RS and partition coefficient - Devi Wilfred, C. (Elsevier Ltd, 2013)
A range of ionic liquids (ILS) with different cation and anion had been investigated for its ability to extract dibenzothiophene (DBT) from n-dodecane through COSMO-RS prediction and experiment. COSMO-RS showed quinolinium-based ILs as one of the potential ILs for hydrocarbon desulfurization. In real experiment, 1-butyl-6-methylquinolinium thiocyanate and 1-butyl-6-methylquinoliniumdicyanamide were synthesized and have shown to have the highest desulfurization efficiency in model oil among the ILs investigated. Â© 2013 Elsevier Ltd.